The role of mechanically sensitive ion channel Piezo1 in bone remodeling - Du, Yugui; Xu, Bowen; Li, Quiying; Peng, Chuhan; Yang, Kai (Frontiers in Bioengineering and Biotechnology, 2024)
Piezo1 (2010) was identified as a mechanically activated cation channel capable of sensing various physical forces, such as tension, osmotic pressure, and shear force. Piezo1 mediates mechanosensory transduction in different organs and tissues, including its role in maintaining bone homeostasis. This review aimed to summarize the function and possible mechanism of Piezo1 in the mechanical receptor cells in bone tissue. We found that it is a potential therapeutic target for the treatment of bone diseases.